Resiko Ergonomi Pengolahan Kripik Balado Menggunakan Metode Rapid Entire Body Assessment - Adha, Parlan Hariyono (Universitas Putra Indonesia YPTK Padang, 2024)
Complaints of Musculoskeletal Disorders (MSDs) are complaints in certain muscle parts that are often experienced by workers. Some jobs that can be the cause of MSDS such as jobs that are done repeatedly, work for a long time with no changing positions. This research adopts a survey methodology, and primary data is collected for analysis. The data source for this study is the Habil Snack SME. The measurements conducted in the study revealed that six work postures were categorized as high risk. These included activities such as opening cassava, washing cassava, cassava carving, mixing chili, packaging, and weighing. On the other hand, five work postures, namely cassava cutting, frying, brushing, pressing, and packing, were classified as medium risk. The purpose of this study is to determine the work posture in the activity of making Balado chips from the Habil Snack Usaha Kecil Menengah (UKM) using the Rapid Entire Body Assessment (REBA) method and to find out the proposed form of improving work posture so that the operator feels comfortable at work. The type of research in this study is a survey. The type of data in this study is primary data. The source of the data in this research comes from UKM Habil Snack. The results of the measurements carried out can be concluded that there are 6 work postures with high categories, namely opening cassava activities, washing cassava activities, cassava carving activities, mixing chili activities, packaging activities, and weighing activities. While the other 5 work postures are in the medium category, namely cassava cutting activities, frying activities, brushing activities, pressing activities, and packing activities are in the medium category.